1966
DOI: 10.1126/science.153.3743.1539
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobins in Sheep: Multiple Differences in Amino Acid Sequences of Three Beta-Chains and Possible Origins

Abstract: Among the three adult sheep hemoglobins (A, B, and C), two (A and B) are reportedly products of alleles. The beta-chains of A and B differ by at least seven scattered amino acid residues whereas the beta-sequence of C differs from A by at least 16 residues and from B by at least 21 residues. These changes suggest that the origin of C-beta antedated the divergence of A and B. Five shared differences between A-beta and C-beta with respect to B-beta can be interpreted as the result of selective advantage in favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…However, despite the large number of ,B-chain sequences listed by Eck and Dayhoff (1966), only those for human (Goldstein, Konigsberg, and Hill 1963), sheep (Boyer et al 1967), and cattle ) have been completely characterized. A sequence for rabbit ,B-chain has been published (Braunitzer et al 1966) but experimental details were not given, and in view of discrepancies between this sequence and the partial sequence of Naughton and Dintzis (1962) a comparison of rabbit ~-globin with other ~-chains will not be attempted here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the large number of ,B-chain sequences listed by Eck and Dayhoff (1966), only those for human (Goldstein, Konigsberg, and Hill 1963), sheep (Boyer et al 1967), and cattle ) have been completely characterized. A sequence for rabbit ,B-chain has been published (Braunitzer et al 1966) but experimental details were not given, and in view of discrepancies between this sequence and the partial sequence of Naughton and Dintzis (1962) a comparison of rabbit ~-globin with other ~-chains will not be attempted here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous workers have experienced difficulties with this hydrophobic area ofthe globin chains. Thus Boyer et al (1967) and Babin et al (1966) found the peptide equivalent to ,8Tp12 in sheep ,8-and bovine y-chains was insoluble and difficult to purify and their sequence data for this area is the least satisfying in their work. The ,8Tp12 peptide from human ,8-chain after performic acid oxidation (Goldstein, et al 1961) was soluble and could be purified on sulphonated polystyrene.…”
Section: Leu-leu-gly-asn-ile-ile-val-ile-cys-leu-ala-glu-his-phe-gly-lysmentioning
confidence: 99%
“…Hb-C becomes a major haemoglobin in animals severely anaemic from blood loss by replacing Hb-A but not Hb-B. The s-chain ofHb-C is composed of 141 residues and differs from the pA-chain by at least 16 residues and from the ,B-chain by at least 21 residues (Beale et al 1966;Boyer et al 1966Boyer et al , 1967Wilson et al 1966). A similar phenomenon is also observed in the domestic goat (Huisman, Adams, Dimmock, Edwards & Wilson, 1967 (Huisman, van Viet & Sebens, 1958;Meyer, 1967) have indicated a marked variability in several species.…”
Section: Originatedmentioning
confidence: 99%
“…The primary structures of the ,-chains of the two adult sheep haemoglobin types, designated as Hb-A* and Hb-B, have recently been determined (Beale, Lehmann, Drury & Tucker, 1966;Boyer et al 1966Boyer et al , 1967Huisman, Reynolds, Dozy & Wilson, 1965; Wilson, Edwards, McDaniel, Dobbs & Huisman, 1966). The two polypeptide chains are each composed of 145 residues; they differ by at least seven residues, which are located in positions 50, 58, 75, 76, 120, 129 and 144, counted from the N-terminal end (indicated as position 2).…”
Section: Originatedmentioning
confidence: 99%
See 1 more Smart Citation